Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises: 69

Answer

$12 + 9i$

Work Step by Step

$3i(2 - i)^2= 3i(4 -2i - 2i + i^2) = 3i(4 - 4i + (-1)) $ $= 3i(3 - 4i) = 9i - 12i^2 = 3i - 12(-1) = 12 + 9i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.